Management of ulcerative colitis in a real-life setting: An Italian multicenter, prospective, observational AIGO study. Issue 3 (March 2019) - Scribano, Maria Lia; Papi, Claudio; Costa, Francesco; Bortoli, Aurora; Bortoluzzi, Francesco; Buscarini, Elisabetta; Cappello, Maria; Caserta, Luigi; Cortelezzi, Claudio; Ferronato, Antonio; Manguso, Francesco; Mazzuoli, Silvia; et al.
Abstract: Background: No data are available on the variability in the clinical management of ulcerative colitis (UC) patients by Italian gastroenterologists. Therefore, improving the standards of UC care as provided by the National Welfare Clinical Path (PDTA), in accordance with the European Crohn's and Colitis Organization (ECCO) guidelines for UC, is not easy. Aims: To assess the management of UC by Italian gastroenterologists in a real-life setting taking into account its variability. Methods: This prospective, cross-sectional, observational study included IBD-specialized gastroenterologists (GSIBDs) and general gastroenterologists (GGs) working in Italian public hospital units. Consecutive patients with an UC flare were enrolled and the medical treatment evaluated. For each center, the physician in charge of the study (16 GSIBDs and 10 GGs) was administered two electronic questionnaires. Results: Among 26 units, 573 UC patients were enrolled. Good adherence to the European guidelines was reported; GSIBDs reported greater adherence than GGs with a higher prescription of rectal and combination therapy in mild to moderate distal disease and a higher rate of hospitalization in severe UC. Conclusion: The management of UC by Italian gastroenterologists in clinical practice is good according to the ECCO consensus recommendations, though some discrepancies are present between GSIBDs and GGs.